The effects of vitamin E on some haematological and biochemical values in the lambs - Naziro?lu, Mustafa; Çay, Mehmet; Aksakal, Mesut; Akgül, Emin (Scientific and Technical Research Council of Turkey, 1996)
This study has been done to determine the effect of vitamin E on some blood haematological and biochemical values in lambs. Four Akkaraman lambs were fed with vitamin E (DL-? tocopheryl acetate) supplemented diet (250 mg/kg feed) and four lambs were used as control. The blood biochemical and haematological values were measured at 1, 2, 4, 6 and 10 weeks. The blood ammonia nitrogen levels of all lambs were measured weekly intervals and at three times (Before feeding and at the 3rd and 6th hours after feeding). The haemoglobin and serum glucose levels were higher (p<0.05) and the activity of LDH levels were lower (P<0.01) in vitamin E supplemented, lambs than those of control. The blood ammonia nitrogen levels at the 6th hours after feeding were higher levels in vitamin E supplemented group than that of control (P<0.01). Vitamin E supplementation did not cause any changes on white blood cells and red blood cells counts and packet cell volume. MCV, MCH, MCHC, Erythrocyte Osmotic Fraglity and the activity of ALP,Amylase, SGPT, CK, ASP, SGOT and levels of Cholesterol, T. Protein, Uric Acid, Triglycerides, Urea Nitrogen, Creatinene, Albumin. Ca,++ Chloride, Phosphorus,Inorganic Phosphorus Na+ and K+. It was observed that the supplementation of vitamin E were raised haemoglobins and serum glucose levels and the 6th hours after feeding of the blood ammonia nitrogen levels. On the other hand the activity of LDH levels were seemed to be decreasing.
Kuzularda E Vitamininin Bazi Hematolojik ve Biyokimyasal De?erlere Etkisi
Keywords: Biochemical levels; Blood ammonia nitrogen; Haemotological values; Lambs; Vitamin E